2021
DOI: 10.1002/aws2.1258
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized bio‐adsorbents for removal of perfluoroalkyl substances: A perspective

Abstract: Poly-and perfluoroalkyl substances (PFAS) are known as "forever chemicals" due to their ubiquitous persistence in the environment, and their negative human health effects. Among them, short-chain PFAS are of increasing concern due to their high solubility and mobility in water, while possessing persistency and toxicity nature like their longer-chain analogs. The most common method for PFAS removal from water is by sorption with activated carbons or ion exchange resins, but these adsorbents only exhibit limited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 102 publications
(197 reference statements)
0
5
0
Order By: Relevance
“…14,15 The electrostatic interaction as the dominant PFAS removal mechanism has been reported in some cationic amine-containing organic adsorbents, which also exhibited the rapid PFAS removal kinetics. 19,20,36,47,48 Park et al investigated the PFAS removal performance in magnetic ion-exchange resins to understand the role of the charge interaction. 37 Surprisingly, PFOS and its branched isomer with different hydrophobicity showed almost equal equilibrium uptake due to their similar total atomic charge.…”
Section: Pfas Removal Mechanism By Qncmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 The electrostatic interaction as the dominant PFAS removal mechanism has been reported in some cationic amine-containing organic adsorbents, which also exhibited the rapid PFAS removal kinetics. 19,20,36,47,48 Park et al investigated the PFAS removal performance in magnetic ion-exchange resins to understand the role of the charge interaction. 37 Surprisingly, PFOS and its branched isomer with different hydrophobicity showed almost equal equilibrium uptake due to their similar total atomic charge.…”
Section: Pfas Removal Mechanism By Qncmentioning
confidence: 99%
“…18 However, very limited studies have been reported for PFAS remediation using cellulosic adsorbents. 19 To design an effective adsorbent based on the concept of nanocellulose scaffold, we consider two primary PFAS removal mechanisms: (i) hydrophobic attraction between the scaffold and C–F chains, and (ii) electrostatic attraction between the anionic functional groups in PFASs and cationic functional sites on the scaffold. Previously, some groups suggested that electrostatic attraction is the dominant adsorption mechanism for the short-chain PFAS removal, while hydrophobicity is the dominant adsorption mechanism for the long chain PFAS removal.…”
Section: Introductionmentioning
confidence: 99%
“…A media's acceptability is a function of many issues such as performance, cost, operational requirements, impacts on general water quality, and regulatory acceptance. In this topical collection, Li et al (2021) review and discuss the potential of using functional bioadsorbents as low-cost alternatives to traditional adsorbents, and of particular interest is their potential removal of short-chain PFAS. The authors state that nano-scale biosorbents can be derived and properly functionalized in a cost-effective manner from raw biomass.…”
Section: Novel Adsorbentsmentioning
confidence: 99%
“…While several reviews have addressed adsorption technology and novel adsorbents for PFAS removal, , there has yet to be a comprehensive critical review specifically focused on comparing and evaluating the adsorption behaviors of PFAS on novel and modified adsorbents. This assessment would be particularly valuable for distinguishing these innovative materials from other high-performing adsorbents, such as activated carbon.…”
Section: Introductionmentioning
confidence: 99%